Safety and efficacy of nilotinib in routine clinical practice in patients with chronic myeloid leukemia in chronic or accelerated phase with resistance or intolerance to imatinib: results from the NOVEL study. (March 2018) - Kuo, Ching-Yuan; Wang, Po-Nan; Hwang, Wen-Li; Tzeng, Cheng-Hwai; Bai, Li-Yaun; Tang, Jih-Luh; Chang, Ming-Chih; Lin, Sheng-Fung; Chen, Tsai-Yun; Chen, Yeu-Chin; Tan, Tran-Der; Hsieh, Chih-Yi; et al.
Background: Nilotinib, a second-generation tyrosine kinase inhibitor (TKI), is approved for the treatment of patients with chronic myeloid leukemia (CML) in many countries, including Taiwan. Though a number of controlled clinical trials have demonstrated the safety and efficacy of nilotinib, studies assessing the safety and efficacy of nilotinib in routine clinical practice are limited. Methods: The current study was an open-label, single-arm study conducted across 12 centers in Taiwan in adult patients with CML in chronic or accelerated phase with confirmed Ph+ chromosome (or BCR-ABL) and resistant or intolerant to one or more previous TKIs. The primary objective was to collect the long-term safety data in patients treated with nilotinib 400 mg, twice daily for up to 2 years. Results: The study enrolled 85 patients with CML, including 76 in the chronic phase (CML-CP) and 9 in the accelerated phase (CML-AP). Overall, 1166 adverse events (AEs) were reported in 80 patients (94.1%), of which 70 AEs (6%) in 28 patients (32.9%) were serious and 336 AEs (28.8%) reported in 60 patients (70.6%) were drug-related. Common drug-related AEs were thrombocytopenia (21.2%), increased alanine aminotransferase (21.2%) and pruritus (17.7%). Of the 85 patients, 19 switched from imatinib due to intolerance – AEs were resolved in 16 of these 19 patients (84.2%). By 24 months, the cumulative rates of complete cytogenetic response (CCyR), major molecular response (MMR), MR4.0 ( BCR-ABL1 IS ⩽0.01%) and MR4.5 ( BCR-ABL1 IS ⩽0.0032%) were 75.3, 56.8, 16.2 and 7.4%, respectively. Patients with CML-CP at baseline had higher overall survival (OS) and progression-free survival (PFS) than those with CML-AP. Conclusion: This is the first study that demonstrated that nilotinib is effective and well-tolerated in patients resistant or intolerant to imatinib in the real-world setting in Taiwan, reflecting effective management of CML by physicians under routine clinical practice in Taiwan.